A revision of the genus Conocrinus d’Orbigny, 1850 (Echinodermata, Crinoidea, Rhizocrinidae) and its place among extant and fossil crinoids with a xenomorphic stalk - Roux, Michel; Eléaume, Marc; Améziane, Nadia (Zootaxa, 2019)
The genus Conocrinus d’Orbigny, 1850 (Crinoidea, Bourgueticrinina) was established on the basis of two aboral cups that had previously been described as Bourgueticrinus thorenti d’Archiac, 1846. One of these (now considered lost) came from the “Rocher du Goulet” at the base of the Biarritz section (Bartonian, Côte des Basques, southwest France). D’Archiac figured only the second cup; this belongs to the d’Orbigny Collection and is still housed in the palaeontological collection of the Muséum national d’Histoire naturelle (Paris) as the lectotype of the species, C. thorenti. It appears that it was collected from Priabonian levels exposed near Castellane (Alpes de Haute Provence, southeast France). New observations on this cup, as well as a detailed study of the characters of aboral cups, columnals and proximal brachials in a few extant and fossil species classically attributed to Conocrinus or to closely related genera such as Democrinus, Rhizocrinus and Tormocrinus, have yielded arguments for a revision of the taxonomy and interrelationships of extant and fossil taxa in the family Bourgueticrinidae. Conocrinus (= Tormocrinus), as here interpreted, includes six Eocene species: C. thorenti, C. archiaci, C. cahuzaci n. sp., C. duperrieri, C. cf. suessi and C. veronensis. Numerous extinct species previously attributed to Conocrinus or Democrinus are here transferred to two new genera which first occur in the lower Paleocene: Paraconocrinus n. gen. (type species: P. pyriformis) and Pseudoconocrinus n. gen. (type species: P. doncieuxi). Aboral cups from the “Rocher du Goulet” (Biarritz) are here assigned to Paraconocrinus pellati n. gen., n. sp., while the Danian species Democrinus maximus is transferred to Pseudoconocrinus n. gen. A new genus, Cherbonniericrinus, is created to accommodate a single extant species, Ch. cherbonnieri, previously attributed to Conocrinus, while the extant genus Rhizocrinus, closely related to Democrinus, is resurrected. Conocrinus and closely related genera are derived from a bourgueticrinine lineage the first record of which is from the lower Campanian, with the new genus Carstenicrinus. These are all attributed to the family Rhizocrinidae which is here considered distinct from the family Bourgueticrinidae. Rhizocrinids rapidly diversified immediately after the Cretaceous-Paleogene (K/Pg) event. Cretaceous taxa previously placed within the family Bourgueticrinidae now appear to be polyphyletic. Some of them do not belong to Bourgueticrinina, such as those of the Dunnicrinus lineage. Interrelationships of Rhizocrinidae and other post-Palaeozoic families having a xenomorphic stalk are discussed.